The Efficiency of Active Forms of the Unemployment Reduction - Sylwia Guzdek (Contemporary Economics)
The problem of unemployment appeared from special intensification in Poland after 1989, when began the transformation of economic system. At the beginning any active forms of the unemployment reduction were used. The attention was focused only on appeasement its results. From 1997 we could observe the growth of utilization the active methods of the unemployment reduction. In the article the scale of unemployment structure in Wadowice district and analysis of active forms of unemployment reduction efficiency during period 1999–2006 are presenting.